HUBUNGAN MODEL PENDEKATAN DAN STRATEGI PEMBELAJARAN DENGAN FILSAFAT SERTA TEORI BELAJAR DALAM PEMBELAJARAN DI SD/MI - Elfa Mutiya (Jurnal Salome : Multidisipliner Keilmuan, 2026)
This study examines the relationship between learning models, approaches, and strategies with educational philosophy and learning theories in elementary schools (SD/MI). The discussion emphasizes how philosophical foundations and learning theories guide teachers in selecting and integrating models, approaches, and strategies to create effective and meaningful learning experiences. The analysis is based entirely on literature review from relevant educational books, focusing on both theoretical and practical perspectives. Findings show that integrating philosophy, learning theory, and practical methods enhances students’ cognitive, social, and emotional development, while making learning more engaging and structured. This study provides insights for teachers to design learning processes that are systematic, student-centered, and aligned with educational goals.